HIV-I : molecular biology and pathogenesis : clinical applications - August, J. Thomas.; Murad, Ferid.; Jeang, Kuan-Teh. (Advances in pharmacology, 2008)
Although it is one of the most-widely studied viruses, many mysteries still remain about HIV. Covering the latest advances and challenges associated with clinical application of new antiviral drugs and vaccines, this revised edition is a companion to Murad:HIV-1: Molecular Biology and Pathogenesis, 2E. Leading investigators in HIV research present a timely picture of the molecular mechanisms which guide HIV-1 expression and replication and provide the most current clinical strategies for combating this virus. * The latest developments in HIV-vaccine research * New concepts in the discovery and design of novel anti-HIV drugs.